Al di là del metodo. L’empatia a partire da Jean-Paul Sartre - Adinolfi, Ciro (Bollettino Filosofico, 2022)
In this essay we intend to reread the problem of empathy starting from some Sartrean considerations, expressed in the last phase of his reflection. Sartre conceives empathy as the necessary methodology for understanding a man. However, after having analysed the meaning of this method, which we call empathic method, we want to propose a rethinking of what we consider to be the other side of this method, which we will call methodical empathy. We will see how these two elements constitute two perspectives on the same event, which is the relationship to otherness. After having understood and articulated this dualism, we will propose some ethical reflections in the direction of the notion of love. Keywords: Biography, Empathy, Ethics, Sartre, Writing